Water-soluble base oil composition

By using acrylic resins with different glass transition temperatures and molecular weights in the water-soluble base oil composition, the problem of slow drying speed of traditional water-based coatings is solved, and a coating film with high color, high brightness and excellent mechanical and physical properties is achieved, which is suitable for vehicle body coating.

CN119816570APending Publication Date: 2025-04-11KCC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380063294.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-08
Filing Date
2023-09-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The traditional water-based coloring base coating compositions dry slowly, resulting in reduced volume shrinkage, reduced brightness, and may lead to precipitation of pigments or solid powders, affecting the gloss and durability of the coating film.

Method used

Using a water-soluble base oil composition containing the first acrylic resin and the second acrylic resin, the drying speed and crosslinking density of the coating film are improved by adjusting the glass transition temperature and molecular weight of the resin, thereby improving the appearance characteristics and mechanical and physical properties of the coating film.

Benefits of technology

It realizes a high color and brightness coating, with excellent mechanical and physical properties, including gloss, impact resistance, water resistance and cold fracture resistance, and is suitable for vehicle body coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005293652620000161
    Figure BDA0005293652620000161
  • Figure BDA0005293652620000171
    Figure BDA0005293652620000171
  • Figure BDA0005293652620000172
    Figure BDA0005293652620000172
Patent Text Reader

Abstract

The present invention relates to a water-soluble base oil composition comprising a first acrylic resin having a glass transition temperature of 15 to 25 DEG C and a weight average molecular weight of 11,000 to 15,000 g / mol, a second acrylic resin having a glass transition temperature of 15 to 25 DEG C and a weight average molecular weight of 10,000 to 10,000 g / mol, a polyurethane dispersion resin, a polyester resin, a polyurethane resin, and a melamine-based curing agent. The second acrylic resin has a glass transition temperature of 1 to 10 DEG C and a weight average molecular weight of 5,000 to 10,000 g / mol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a water-soluble base oil composition. Background Art

[0002] Generally, the coating film on the vehicle body should not deteriorate or rust, and should have the durability to maintain the gloss or color of the coating film. Therefore, the coating process of the vehicle usually performs electrolytic deposition coating on the vehicle body that has undergone the pretreatment process, and then implements mid-coating to improve the tightness and flatness. For the beauty of the vehicle body, a primer coating is implemented on the vehicle body that has undergone the mid-coating. Then, in order to maintain the color of the primer, improve the appearance, and protect the primer from external damage, a clear coat is usually applied. In addition, among the important advertising slogans used in various industries recently, environmental protection has become a specific form of actively limiting the use of volatile organic compounds.

[0003] The volatile organic compounds are easy to volatilize at room temperature. When they exist in gaseous state, they are naturally emitted into the atmosphere, becoming an important cause of air pollution. It is reported that such volatile organic compounds contain inherent biological toxicity and chemical reactivity, which may induce various forms of environmental problems, and may become the cause of the formation of the ozone layer in the troposphere and the destruction of the stratospheric layer, which will seriously damage the environment, such as the emergence of greenhouse effect and the occurrence of odor.

[0004] In view of this, in order to improve environmental protection, the automotive coating field is also transitioning from solvent-based coating compositions to water-based coating compositions, and recently, it is transitioning to water-based metallic coloring coating compositions instead of solvent-based metallic coloring base coating compositions.

[0005] In this regard, Korean registered patent No. 1,221,276 (Patent Document 1) discloses a water-based base oil coating composition comprising a polyurethane dispersion resin, an acrylic emulsion resin, a pigment, a leveling agent, a silicone defoamer, an ultraviolet absorber, an ultraviolet stabilizer, a dispersant, ionized water, and a thickener. However, as in Patent Document 1, the conventional water-based color base coating composition has a slow drying speed, and has the following problems: drying causes a decrease in volume shrinkage and reduces brightness, or causes a decrease in the solvent content in the composition and reduces brightness, and also causes precipitation of the pigment or solid powder in the composition.

[0006] Therefore, it is actually necessary to research and develop a water-based base coating composition with the following characteristics: fast drying speed, prevention of volume shrinkage due to drying and reduced brightness, improvement of brightness reduction caused by reduction of organic solvent content in the composition, reduction of organic solvent content to achieve VOC emission reduction and environmental protection, and no problem of pigment or solid powder precipitation in the composition.

[0007]

Prior technical literature

[0008] [Patent Literature]

[0009] (Patent Document 1) Korean registered patent No. 10-1221276 (January 11, 2013) Summary of the invention

[0010] Issues to be solved

[0011] The present invention provides a water-soluble primer composition, which can prevent deformation of a coating film, wherein the coating film is formed by reducing volume shrinkage through drying, thereby achieving high chroma and high brightness, and preparing a coating film with excellent mechanical and physical properties.

[0012] Problem Solution

[0013] One aspect of the present invention can provide a water-soluble primer composition comprising a first acrylic resin, a second acrylic resin, a polyurethane dispersion resin, a polyester resin, a polyurethane resin, and a melamine-based curing agent.

[0014] Effects of the Invention

[0015] The water-soluble primer composition of the present invention contains resins with different drying speeds to prevent deformation of the coating film. The coating film is formed by reducing volume shrinkage through drying, thereby achieving high chroma and high brightness. In addition, the coating film made of the composition has excellent mechanical and physical properties, especially excellent physical properties such as gloss, impact resistance, water resistance, and cold-crack resistance, and can be well suitable for vehicle body coating. DETAILED DESCRIPTION

[0016] Hereinafter, the present invention is described in detail.

[0017] One aspect of the present invention provides a water-soluble primer composition, which comprises a first acrylic resin, a second acrylic resin, a polyurethane dispersion resin, a polyester resin, a polyurethane resin and a melamine-based curing agent, wherein the first acrylic resin has a glass transition temperature of 15 to 25° C. and a weight average molecular weight of 11,000 to 15,000 g / mol, and the second acrylic resin has a glass transition temperature of 1 to 10° C. and a weight average molecular weight of 5,000 to 10,000 g / mol.

[0018] As described above, when two acrylic resins with different glass transition temperatures and weight average molecular weights are used, the drying speed and crosslinking density of the coating film are adjusted, the appearance characteristics and mechanical physical properties of the coating film are improved, the organic solvent content in the composition is low, environmentally friendly, and has excellent operability.

[0019] For example, the different glass transition temperatures of the two acrylic resins can adjust the coating drying speed and surface tension of the water-soluble primer composition of the present invention, achieve high chroma and high brightness, and have excellent coating appearance characteristics. In addition, the different weight average molecular weights of the two acrylic resins can adjust the crosslinking density of the coating, thereby improving adhesion and mechanical and physical properties.

[0020] First acrylic resin

[0021] The first acrylic resin has the function of improving the rheological property and hardness of the coating film, and the coating film is made of a water-soluble base oil composition containing the first acrylic resin.

[0022] The first acrylic resin may be a product directly synthesized by a known method or a commercially available product. For example, the first acrylic resin may include one or more monomer-derived units selected from the group consisting of allyl methacrylate (AMA), methyl methacrylate (MMA), ethyl acrylate (EA), hydroxyethyl acrylate (HEA) and methacrylic acid (MAA). For example, the first acrylic resin may be a mixture of allyl methacrylate (AMA), methyl methacrylate (MMA), ethyl acrylate (EA), hydroxyethyl acrylate (HEA) and methacrylic acid (MAA) as a monomer.

[0023] In addition, the mixture may further include a divalent acrylic acid monomer. For example, the divalent acrylic acid monomer may be 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, 1,5-pentanediol dimethacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol diacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, and the like.

[0024] The solid powder content (NV) of the first acrylic resin can be 32 to 38% by weight or 34 to 36% by weight relative to the total weight of the resin. When the solid powder content of the first acrylic resin is within the above range, the storage stability of the resin can be improved and the operability is excellent. When the solid powder content of the first acrylic resin is lower than the above range, the viscosity is too low, which will cause the water-soluble base oil composition containing it to have insufficient operability. When it exceeds the above range, the viscosity of the first acrylic resin is too high, resulting in reduced stability in the reaction, poor dispersion stability, and flocculation after a period of time.

[0025] The viscosity of the first acrylic resin at 25°C may be 8 to 320 cps or 10 to 300 cps. When the viscosity of the first acrylic resin at 25°C is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the viscosity of the first acrylic resin at 25°C is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0026] The acid value (Av) of the first acrylic resin may be 1 to 10 mgKOH / g or 3 to 10 mgKOH / g. When the acid value of the first acrylic resin is within the above range, the reactivity of the composition containing it can be adjusted, thereby improving the appearance characteristics of the coating film. When the acid value of the first acrylic resin is lower than the above range, the stability of the resin decreases, and there is a problem of decreased storage of the coating composition. When it exceeds the above range, the flocculation of the resin is enhanced, resulting in an increase in the viscosity of the composition, and there is a problem of decreased operability and water resistance of the coating film.

[0027] The hydroxyl value (OHv) of the first acrylic resin may be 11 to 20 mgKOH / g or 11 to 17 mgKOH / g. When the hydroxyl value of the first acrylic resin is within the above range, the reactivity of the composition containing it can be adjusted, thereby improving the appearance characteristics of the coating film. When the hydroxyl value of the first acrylic resin is lower than the above range, the stability of the resin is reduced, and there is a problem of reduced storage of the coating composition. When it exceeds the above range, the flocculation of the resin is enhanced, resulting in an increase in the viscosity of the composition, and there is a problem of reduced operability and water resistance of the coating film.

[0028] The pH of the first acrylic resin may be 6 to 10 or 7 to 9. When the pH of the first acrylic resin is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the pH of the first acrylic resin is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0029] The glass transition temperature (Tg) of the first acrylic resin may be 15 to 25° C. or 16 to 20° C. When the glass transition temperature of the first acrylic resin is within the above range, the hardness and appearance characteristics of the coating film made of the composition containing it are improved. When the glass transition temperature of the first acrylic resin is lower than the above range, the drying speed and crosslinking density of the coating film decrease, and there is a problem of insufficient hardness and appearance characteristics of the coating film. When it exceeds the above range, the coating film becomes brittle, which leads to insufficient appearance characteristics and chipping resistance of the coating film.

[0030] The weight average molecular weight (Mw) of the first acrylic resin may be 11,000 to 15,000 g / mol or 12,500 to 14,500 g / mol. When the weight average molecular weight of the first acrylic resin is within the above range, the durability, adhesion, hardness, weather resistance and other long-term physical properties of the coating film may be excellent. When the weight average molecular weight of the first acrylic resin is lower than the above range, the molecular weight is small, so that the water resistance, weather resistance and scratch resistance of the coating film may be insufficient, and when it exceeds the above range, the molecular weight may increase and the fluidity may decrease, which may make the operability of the water-soluble base oil composition containing it poor, the surface flatness may be poor, and it may be difficult to prepare a coating film with excellent appearance.

[0031] The first acrylic resin may be in the form of an emulsion dispersed in a solvent such as deionized water. For example, the first acrylic resin may be in the form of an emulsion dispersed in a solvent, and the average diameter may be 70 to 170 nm or 80 to 160 nm. When the first acrylic resin is in the form of an emulsion dispersed in deionized water, the volatile organic compound (VOC) content of the coating may be reduced. When the average diameter is within the above range, the appearance and the stability of the coating are good.

[0032] Based on the total weight of the water-soluble primer composition, the first acrylic resin may be included in the composition in an amount of 3 to 17 wt%, 5 to 15 wt%, or 7 to 13 wt%. When the first acrylic resin is included in the above content range, it has the effect of improving the coating film adhesion, durability, hardness, and scratch resistance. When the content of the first acrylic resin is lower than the above range, the drying property decreases, and there is a problem of decreased coating film adhesion, gloss, hardness, and durability. When it exceeds the above range, it dries quickly, resulting in insufficient coating operability and paint fluidity of the composition, and the problem of decreased coating film appearance and scratch resistance occurs.

[0033] Second acrylic resin

[0034] The second acrylic resin has the function of improving the rheological property and hardness of the coating film, and the coating film is made of the water-soluble base oil composition containing the second acrylic resin.

[0035] The technical features of the second acrylic resin may be the same as described for the first acrylic resin except for the following.

[0036] The solid powder content (NV) of the second acrylic resin can be 42 to 50% by weight or 45 to 47% by weight of the total weight of the resin. When the solid powder content of the second acrylic resin is within the above range, the storage stability of the resin can be improved, and the operability is excellent. When the solid powder content of the second acrylic resin is lower than the above range, the viscosity becomes too low, and there is a problem of insufficient operability of the water-soluble base oil composition containing it, and when it exceeds the above range, the viscosity of the second acrylic resin is too high, resulting in decreased stability in the reaction and poor dispersion stability. Therefore, flocculation may occur after a period of time.

[0037] The viscosity of the second acrylic resin at 25°C may be 180 to 550 cps or 200 to 500 cps. When the viscosity of the second acrylic resin at 25°C is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the viscosity of the second acrylic resin at 25°C is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0038] The acid value (Av) of the second acrylic resin may be 11 to 20 mgKOH / g or 12 to 18 mgKOH / g. When the acid value of the second acrylic resin is within the above range, the reactivity of the composition containing it can be adjusted, thereby improving the appearance characteristics of the coating film. When the acid value of the second acrylic resin is lower than the above range, the stability of the resin decreases, and there is a problem of decreased storage of the coating composition, while when it exceeds the above range, the flocculation of the resin is enhanced, resulting in an increase in the viscosity of the composition, and there is a problem of decreased operability and water resistance of the coating film.

[0039] The hydroxyl value (OHv) of the second acrylic resin may be 1 to 10 mgKOH / g or 2 to 9 mgKOH / g. When the hydroxyl value of the second acrylic resin is within the above range, the reactivity of the composition containing it can be adjusted, thereby improving the appearance characteristics of the coating film. When the hydroxyl value of the second acrylic resin is lower than the above range, the stability of the resin is reduced, and there is a problem of decreased storage of the coating composition. When it exceeds the above range, the flocculation of the resin is enhanced, resulting in an increase in the viscosity of the composition, and there is a problem of decreased operability and water resistance of the coating film.

[0040] The pH of the second acrylic resin may be 7 to 9 or 7.5 to 8.5. When the pH of the second acrylic resin is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the pH of the second acrylic resin is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0041] The glass transition temperature (Tg) of the second acrylic resin may be 1 to 10° C. or 2 to 9° C. When the glass transition temperature of the second acrylic resin is within the above range, the hardness and appearance characteristics of the coating film made of the composition containing it are improved. When the glass transition temperature of the second acrylic resin is lower than the above range, the drying speed and crosslinking density of the coating film decrease, and there is a problem of insufficient hardness and appearance characteristics of the coating film. When it exceeds the above range, the coating film becomes brittle, which leads to insufficient appearance characteristics and chipping resistance of the coating film.

[0042] The weight average molecular weight (Mw) of the second acrylic resin may be 5,000 to 10,000 g / mol or 6,000 to 9,000 g / mol. When the weight average molecular weight of the second acrylic resin is within the above range, the durability, adhesion, hardness, weather resistance and other long-term physical properties of the coating film may be excellent. When the weight average molecular weight of the second acrylic resin is lower than the above range, the molecular weight is small, so that the water resistance, weather resistance and scratch resistance of the coating film may be insufficient, and when it exceeds the above range, the molecular weight may increase and the fluidity may decrease, which may make the operability of the water-soluble base oil composition containing it poor, the surface flatness may be poor, and it may be difficult to prepare a coating film with excellent appearance.

[0043] The second acrylic resin may be in the form of an emulsion dispersed in a solvent such as deionized water. For example, when the second acrylic resin is in the form of an emulsion dispersed in deionized water, it has the effect of reducing the content of volatile organic compounds (VOC) in the coating.

[0044] Based on the total weight of the water-soluble primer composition, the second acrylic resin can be included in the composition in an amount of 3 to 17 wt%, 5 to 15 wt%, or 7 to 13 wt%. When the second acrylic resin is included in the above content range, it has the effect of improving the coating film's adhesion, durability, hardness, and scratch resistance. When the content of the second acrylic resin is lower than the above range, the drying property decreases, and there is a problem of decreased coating film adhesion, gloss, hardness, and durability. When it exceeds the above range, it dries quickly, resulting in insufficient coating operability and paint fluidity of the composition, and the problem of decreased coating film appearance and scratch resistance occurs.

[0045] Polyurethane dispersion resin

[0046] The polyurethane dispersion resin has the function of improving the drying properties of a water-soluble base oil composition containing the polyurethane dispersion resin and improving the flexibility of a coating film prepared from the composition.

[0047] The polyurethane dispersion resin may be a polyurethane dispersion resin derived from polyester-polycarbonate. For example, the polyurethane dispersion resin may be a polyurethane dispersion resin derived from polyester-polycarbonate diol.

[0048] The solid powder content (NV) of the polyurethane dispersion resin can be 30 to 40% by weight or 34 to 36% by weight of the total weight of the resin. When the solid powder content of the polyurethane dispersion resin is within the above range, the storage stability of the resin and the storage stability of the water-soluble base oil composition can be improved, and the operability is excellent. When the solid powder content of the polyurethane dispersion resin is lower than the above range, the viscosity becomes too low, and there is a problem of insufficient operability of the water-soluble base oil composition containing it. When it exceeds the above range, the viscosity of the polyurethane dispersion resin is too high, resulting in a decrease in stability during the reaction and a deterioration in dispersion stability. Therefore, flocculation may occur after a period of time.

[0049] The polyurethane dispersion resin may be a form in which the polyurethane resin is dispersed in a solvent. The aqueous medium in which the polyurethane resin is dispersed may be an aqueous solvent or a mixed medium of water and a hydrophilic organic solvent. For example, the aqueous solvent may be tap water, ion exchange water, distilled water, deionized water, etc. In particular, in order to prevent the particles from becoming unstable due to the easy addition of water or the influence of salt, ion exchange water may be used. In addition, the hydrophilic organic solvent may be a low-order monovalent alcohol such as methanol, ethanol, propanol, etc.; a polyvalent alcohol such as glycol, glycerol, etc.; a non-protonic hydrophilic organic solvent such as N-methylmorpholine, dimethyl sulfoxide, dimethylformamide, etc. The polyurethane dispersion resin is in the form of a dispersion dispersed in deionized water, and the average diameter may be 10 to 120 nm or 20 to 100 nm.

[0050] The viscosity of the polyurethane dispersion resin at 25°C may be 5 to 550 cps or 10 to 500 cps. When the viscosity of the polyurethane dispersion resin at 25°C is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the viscosity of the polyurethane dispersion resin at 25°C is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0051] The acid value (Av) of the polyurethane dispersion resin may be 15 to 30 mgKOH / g or 18 to 25 mgKOH / g. When the acid value of the polyurethane dispersion resin is within the above range, the reactivity of the composition containing it can be adjusted, thereby improving the appearance characteristics of the coating film. When the acid value of the polyurethane dispersion resin is lower than the above range, the stability of the resin decreases, and there is a problem of decreased storage of the coating composition. When it exceeds the above range, the flocculation of the resin is enhanced, resulting in an increase in the viscosity of the composition, and there is a problem of decreased operability and water resistance of the coating film.

[0052] The pH of the polyurethane dispersion resin may be 6 to 10 or 7 to 9. When the pH of the polyurethane dispersion resin is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the pH of the polyurethane dispersion resin is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0053] The glass transition temperature (Tg) of the polyurethane dispersion resin may be -45 to -20°C or -40 to -25°C. When the glass transition temperature of the polyurethane dispersion resin is within the above range, the softness and hardness of the coating film are improved. When the glass transition temperature of the polyurethane dispersion resin is lower than the above range, the drying speed of the water-soluble primer composition is delayed, and there is a problem that the solvent resistance and crack resistance of the resulting coating film are insufficient. When the glass transition temperature exceeds the above range, the coating film becomes brittle, which leads to insufficient appearance characteristics and hardness of the coating film.

[0054] The weight average molecular weight of the polyurethane dispersion resin may be 35,000 to 60,000 g / mol or 40,000 to 50,000 g / mol. When the weight average molecular weight of the polyurethane dispersion resin is within the above range, the water-soluble base oil composition has excellent drying properties, cold cracking resistance and impact resistance. When the weight average molecular weight of the polyurethane dispersion resin is lower than the above range, the molecular weight is small, and there is a problem of reduced mechanical and physical properties of the resulting coating film. When the weight average molecular weight exceeds the above range, the molecular weight increases and the fluidity decreases, which makes the coating film brittle, resulting in reduced flatness and reduced scratch resistance.

[0055] Based on the total weight of the water-soluble base oil composition, the polyurethane dispersion resin can be included in the composition in an amount of 0.05 to 7% by weight, 0.1 to 5% by weight, or 0.2 to 3% by weight. When the polyurethane dispersion resin is included in the composition in the above content range, the tensile strength, flexibility, elongation, adhesion, abrasion resistance, scratch resistance, and coating smoothness are improved. When the content of the polyurethane dispersion resin in the composition is lower than the above range, the flexibility decreases, and there is a problem of decreased tensile strength and scratch resistance. When it exceeds the above range, the viscosity of the composition becomes too high, resulting in decreased operability and drying, and the problem of decreased appearance and mechanical physical properties occurs.

[0056] Polyester resin

[0057] The polyester resin has the function of improving the softness and appearance characteristics of the coating film, and the coating film is made of the water-soluble base oil composition containing the polyester resin.

[0058] The polyester resin can be prepared by reacting a carboxylic acid compound with a diol compound. For example, the polyester resin can be prepared by reacting a carboxylic acid compound and a diol compound, wherein the carboxylic acid compound is one or more selected from the group consisting of the following components: adipic acid (AA), isophthalic acid (IPA), trimellitic anhydride (TMA), alicyclic acid, phthalic anhydride, isophthalic acid, terephthalic acid, succinic acid, adipic acid, fumaric acid, maleic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and derivatives thereof; and the diol compound is one or more selected from the group consisting of the following components: 1,6-hexanediol (1,6-HD), neopentyl glycol (NPG), trimethylolpropane (TMP), glycol, propylene glycol, diethylene glycol, butanediol, 1,4-hexanediol, and 3-methylpentanediol.

[0059] The solid powder content (NV) of the polyester resin may be 70 to 90 wt % or 75 to 85 wt % in the total weight of the resin. When the solid powder content of the polyester resin is within the above range, the storage stability of the resin can be improved and the operability is excellent. When the solid powder content of the polyester resin is lower than the above range, the viscosity becomes too low, and there is a problem of insufficient operability of the water-soluble base oil composition containing it, while when it exceeds the above range, the viscosity of the polyester resin is too high, resulting in decreased stability during the reaction.

[0060] The viscosity of the polyester resin at 25°C may be 2,000 to 5,000 cps or 2,200 to 4,700 cps. When the viscosity of the polyester resin at 25°C is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the viscosity of the polyester resin at 25°C is lower than the above range, the viscosity of the composition is too low, the resulting coating film is not formed, and there is a problem of decreased fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of decreased appearance characteristics of the resulting coating film.

[0061] The acid value (Av) of the polyester resin may be 1 to 10 mgKOH / g or 3 to 8 mgKOH / g. When the acid value of the polyester resin is within the above range, the storage stability and crosslinking density of the composition containing it are improved, and a good effect of cold-resistance cracking is achieved. When the acid value of the polyester resin is lower than the above range, the stability of the resin decreases, and there is a problem of decreased storage of the prepared coating composition. When the acid value exceeds the above range, the flocculation of the resin is enhanced, resulting in an increase in the viscosity of the composition, and there is a problem of decreased operability and water resistance of the coating film.

[0062] The hydroxyl value (OHv) of the polyester resin may be 80 to 110 mgKOH / g or 85 to 105 mgKOH / g. When the hydroxyl value of the polyester resin is within the above range, the storage stability and crosslinking density of the composition containing it are improved, and a good effect of cold-resistance cracking is achieved. When the hydroxyl value of the polyester resin is lower than the above range, the stability of the resin is reduced, and there is a problem of decreased storage of the prepared coating composition. When it exceeds the above range, the flocculation of the resin is enhanced, resulting in an increase in the viscosity of the composition, and there is a problem of decreased operability and water resistance of the coating film.

[0063] The glass transition temperature (Tg) of the polyester resin may be -50 to -25°C or -40 to -30°C. When the glass transition temperature of the polyester resin is within the above range, there is an effect of improving the hardness and solvent resistance of the coating film made of the composition containing it. When the glass transition temperature of the polyester resin is lower than the above range, the drying speed and crosslinking density of the coating film decrease, and there is a problem of insufficient hardness and solvent resistance of the resulting coating film, while when it exceeds the above range, the coating film becomes brittle, which leads to insufficient appearance characteristics and chipping resistance of the coating film.

[0064] The weight average molecular weight of the polyester resin may be 6,000 to 12,000 g / mol or 7,000 to 11,000 g / mol. When the weight average molecular weight of the polyester resin is within the above range, the durability, adhesion, hardness, weather resistance and other long-term physical properties of the coating film may be excellent. When the weight average molecular weight of the polyester resin is lower than the above range, the molecular weight is small, and the water resistance, weather resistance and scratch resistance of the coating film may be insufficient. When the weight average molecular weight exceeds the above range, the molecular weight may increase and the fluidity may decrease, which may cause the operability of the water-soluble primer composition containing the same to deteriorate, the surface flatness may be poor, and it may be difficult to prepare a coating film with excellent appearance.

[0065] Based on the total weight of the water-soluble primer composition, the polyester resin may be included in the composition in an amount of 1 to 5% by weight or 2 to 4% by weight. When the polyester resin is included in the above content range, excellent appearance, impact resistance and cold crack resistance can be ensured. When the content of the polyester resin is lower than the above range, the drying property is reduced, and there is a problem of reduced adhesion, gloss, hardness and durability of the coating film. When the content exceeds the above range, the drying is fast, resulting in insufficient coating operability and paint fluidity of the composition, and the problem of reduced appearance and scratch resistance of the coating film occurs.

[0066] Polyurethane resin

[0067] The polyurethane resin has the function of improving the drying properties of a water-soluble base oil composition containing the polyurethane resin and improving the appearance characteristics of a coating film prepared from the composition.

[0068] The polyurethane resin may be a polyurethane diol compound. For example, the polyurethane resin may be a polyurethane diol obtained by reacting a primary amino alcohol, such as aminoethanol or aminoisopropanol; or a primary diamine, such as ethylenediamine, propylenediamine, 2-methyl-pentanediamine-(1,5) or hexamethylenediamine-(1,6); with an alkylene carbonate, such as ethylene or propylene carbonate.

[0069] The solid powder content (NV) of the polyurethane resin can be 30 to 40% by weight or 34 to 36% by weight of the total weight of the resin. When the solid powder content of the polyurethane resin is within the above range, the storage stability of the resin can be improved and the operability is excellent. When the solid powder content of the polyurethane resin is lower than the above range, the viscosity becomes too low, and there is a problem of insufficient operability of the water-soluble base oil composition containing it, and when it exceeds the above range, the viscosity of the polyurethane resin is too high, resulting in decreased stability during the reaction.

[0070] The viscosity of the polyurethane resin at 25°C may be 5 to 600 cps or 10 to 500 cps. When the viscosity of the polyurethane resin at 25°C is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the viscosity of the polyurethane resin at 25°C is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0071] The acid value (Av) of the polyurethane resin may be 15 to 30 mgKOH / g or 18 to 25 mgKOH / g. When the acid value of the polyurethane resin is within the above range, the gloss and appearance characteristics of the coating film are improved. When the acid value of the polyurethane resin is lower than the above range, the stability of the resin decreases, and there is a problem of decreased storage of the coating composition. When the acid value exceeds the above range, the flocculation of the resin increases, resulting in an increase in the viscosity of the composition, and there is a problem of decreased operability and water resistance of the coating film.

[0072] The pH of the polyurethane resin may be 6 to 10 or 7 to 9. When the pH of the polyurethane resin is within the above range, the viscosity of the water-soluble primer composition is appropriate, and the operability is improved. When the pH of the polyurethane resin is lower than the above range, the viscosity of the composition is too low, the coating film is not formed, and there is a problem of reduced fluidity, adhesion and scratch resistance of the paint. When it exceeds the above range, the operability of the composition is insufficient, and there is a problem of reduced appearance characteristics of the coating film.

[0073] The glass transition temperature (Tg) of the polyurethane resin may be -40 to -10°C or -35 to -15°C. When the glass transition temperature of the polyurethane resin is within the above range, the hardness and solvent resistance of the coating film formed from the composition containing the polyurethane resin are improved. When the glass transition temperature of the polyurethane resin is lower than the above range, the drying speed and crosslinking density of the coating film decrease, and there is a problem of insufficient hardness and solvent resistance of the resulting coating film. When the glass transition temperature exceeds the above range, the coating film becomes brittle, which leads to insufficient appearance characteristics and chipping resistance of the resulting coating film.

[0074] The polyurethane resin may be in a dispersed form in a solvent, and the average diameter may be 30 to 110 nm or 40 to 100 nm. When the average diameter of the polyurethane resin is within the above range, the appearance and particle stability are good.

[0075] The weight average molecular weight (Mw) of the polyurethane resin may be 200 to 900 g / mol or 400 to 700 g / mol. When the weight average molecular weight of the polyurethane resin is within the above range, the durability, conformability, hardness, weather resistance and other long-term physical properties of the coating film may be excellent. When the weight average molecular weight of the polyurethane resin is lower than the above range, the molecular weight is small, and the water resistance, weather resistance and scratch resistance of the coating film may be insufficient. When the weight average molecular weight of the polyurethane resin exceeds the above range, the molecular weight may increase and the fluidity may decrease, which may cause the operability of the water-soluble base oil composition containing the polyurethane resin to deteriorate, the surface flatness may be poor, and it may be difficult to prepare a coating film with excellent appearance.

[0076] Based on the total weight of the water-soluble primer composition, the polyurethane resin may be included in the composition in an amount of 1 to 5% by weight or 2 to 4% by weight. When the polyurethane resin content is within the above range, the softness and appearance of the coating film are improved. When the polyurethane resin content is lower than the above range, the drying property is reduced, and there is a problem of reduced adhesion, gloss, hardness and durability of the coating film. When the polyurethane resin content exceeds the above range, the drying is fast, resulting in insufficient coating operability and paint fluidity of the composition, and the appearance and scratch resistance of the coating film are reduced.

[0077] Melamine curing agent

[0078] The melamine-based curing agent has the following function, that is, it can cross-link with various components of the water-soluble primer composition to achieve curing, and can improve the appearance characteristics and gloss of the coating film made of the water-soluble primer composition containing it.

[0079] The melamine curing agent may include a hydrophilic melamine resin containing an imino group. For example, the melamine curing agent may be a liquid containing a hydrophilic melamine resin containing an imino group. In another example, the melamine curing agent contains a hydrophilic melamine resin containing an imino group, and may be a liquid having a solid powder content (NV) of 90 to 98% by weight or 93 to 96% by weight based on the total weight of the melamine curing agent.

[0080] The melamine curing agent products on sale include Cytec's Cymel-325, Cymel-327 and Cymel-385, INEOS's Resimene HM-2608, Resimene 718 and Resimene717, and BASF's Luwipal 052, 072, etc.

[0081] Based on the total weight of the water-soluble primer composition, the melamine curing agent may be included in the composition in an amount of 3 to 8 wt % or 4 to 7 wt %. When the content of the melamine curing agent is within the above range, suitable coating physical properties can be ensured.

[0082] Solvents

[0083] The water-soluble primer composition of the present invention may further include a solvent. The solvent plays a role in adjusting the composition and viscosity and reducing the generation of volatile organic compounds (VOC). For example, the solvent may include one or more water selected from the group consisting of deionized water, purified water, deionized water and distilled water. In addition to water, the solvent may further include an organic solvent.

[0084] The solvent may be contained in the composition in an amount of 20 to 50 wt % or 30 to 40 wt % based on the total weight of the water-soluble primer composition. When the solvent content in the composition is within the above range, it is possible to prevent the problem of decreased water dispersibility of some resins in the composition; the problem of decreased environmental protection, which is the advantage of water-based coatings; and the problem of insufficient evaporation of water, which ultimately causes defects such as pinholes in the coating film and the occurrence of spots.

[0085] pigment

[0086] The water-soluble base oil composition of the present invention may further contain a pigment. The pigment serves to impart color to the prepared coating. For example, the water-soluble base oil composition may be a functional pigment that imparts a metallic effect to the coating, a coloring pigment that is combined with a coating forming substance to impart color and a covering effect, or a combination thereof.

[0087] For example, the functional pigments include aluminum plates treated with water, mica pigments or mixtures thereof. For example, the coloring pigments include oxide-based inorganic pigments, azo (Azo), polycyclic organic pigments containing Vat pigments, anthraquinone-based organic pigments or mixtures thereof.

[0088] Based on the total weight of the water-soluble primer composition, the pigment may be included in the composition in an amount of 15 to 35 wt % or 17 to 32 wt %. When the pigment content in the water-soluble primer composition is within the above range, problems such as insufficient hiding power of the film, decreased stability of the composition, and decreased dispersibility of the pigment can be prevented.

[0089] additive

[0090] The water-soluble base oil composition of the present invention may further comprise: one or more additives selected from the group consisting of a cosolvent, a neutralizer, a catalyst, an ultraviolet absorber, a leveling agent, a defoamer, a wetting agent and a wax.

[0091] The additive may be included in the water-soluble base oil composition in an amount of 2 to 10 wt % or 3 to 9 wt %, based on the total weight of the composition.

[0092] The cosolvent can have the following functions, namely, affect the flatness of the formed coating film, impart storage stability to the water-soluble primer composition, lower the minimum coating film formation temperature, and adjust the volatility of the solvent during coating operation.

[0093] For example, the cosolvent includes ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, propylene glycol, N-methyl-2-pyrrolidone, n-propanol, i-propanol, n-butanol, propylene glycol monomethyl ether, butanediol, hexanediol, 2-ethylhexanol, butyl carbitol, etc., but is not limited to these.

[0094] The neutralizing agent has the function of improving the storage stability of the water-soluble base oil composition and adjusting the pH (pH 7.5 to 9.0).

[0095] For example, the neutralizing agent includes trialkylamines such as trimethylamine, triethylamine and tributylamine; N,N-dialkylalkanolamines such as N,N-dimethylethanolamine, N,N-dimethylpropanolamine, N,N-dipropylethanolamine and 1-dimethylamino-2-methyl-2-propanol; tertiary amine compounds such as trialkanolamines such as N-alkyl-N,N-dialkanolamines and triethanolamine; ammonia; trimethylammonium hydroxide; sodium hydroxide; potassium hydroxide; and lithium hydroxide.

[0096] The catalyst has the following function: preventing the incomplete curing of the water-soluble base oil composition to improve the mechanical and physical properties of the coating film. For example, the catalyst is an amino-containing phosphate compound.

[0097] The UV absorber has the function of blocking ultraviolet rays from reaching the produced coating film, thereby ultimately improving the weather resistance of the coating film.

[0098] The ultraviolet absorber can be a benzotriazole ultraviolet absorber. For example, the benzotriazole ultraviolet absorber includes α-[3-[3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropyl]-ω-hydroxypoly(oxy-1,2-ethanediyl) (α

[0099] -[3-[3-(2H-Benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxo propyl]-ω-hydroxypoly(oxy-1,2-ethanediyl)), α-[3-[3-(2H-Benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxo propyl]-ω-[3-[3-(2H-Benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxo propyl]-ω-hydroxypoly(oxy-1,2-ethanediyl)

[0100] -[3-[3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxop ropoxy]poly(oxy-1,2-ethanediyl)), 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-methyl ester, etc.

[0101] The function of the leveling agent is to impart leveling and wettability to the produced coating film. The leveling agent may be a cationic, anionic or nonionic surfactant, for example, it may include a nonionic surfactant.

[0102] The function of the defoamer is to suppress the generation of bubbles when the coating is manufactured, and to suppress or even eliminate the pinholes or popping caused when the coating is formed. The defoamer is a conventional product that can be used in coating compositions, and there is no particular restriction on its use. For example, the defoamer products on sale include BYK's BYK-011, BYK-015, BYK-072; Air Product's DF-21; Munzing's agitan 281; and San Nopco's Foamster-324.

[0103] The function of the wetting agent is to improve the leveling and wettability of the coating film, and the coating film is made of a composition containing the wetting agent, and there is no particular limitation as long as it is a conventional coating composition. For example, the wetting agent can be a polyether-modified polysiloxane-based or acetylene alcohol-based wetting agent.

[0104] The function of the wax is to prevent sagging due to slow drying, and the coating film is made of a composition containing the wax, and there is no particular limitation as long as it is a conventional coating composition. For example, the wax may be an ethylene-acetate-vinyl ester wax.

[0105] The water-soluble base oil composition of the present invention has a viscosity cup viscosity of 30 to 100 seconds or 50 to 70 seconds at 25° C. based on a No. 4 viscosity cup, and may contain 15 to 50 wt % or 20 to 45 wt % of solid powder based on the total weight of the composition.

[0106] As described above, the water-soluble primer composition of the present invention contains resins with different drying speeds, which can prevent the deformation of the coating film caused by the reduction of volume shrinkage due to drying, and achieve high chroma and high brightness. In addition, the coating film made from the composition has excellent mechanical and physical properties, especially excellent physical properties such as gloss, impact resistance, water resistance, and cold-crack resistance, and can be well applied to vehicle body coating.

[0107] The present invention is described in more detail below by way of examples, but these examples are only used to help understand the present invention, and any meaning thereof will not limit the scope of the present invention by these examples.

[0108] In the present invention, the functional group value of the resin, such as "acid value" and "hydroxyl value", can be detected by a method known in the art, for example, the value detected by titration can be shown.

[0109] The weight average molecular weight of the resin can be measured by a method known in the art, for example, a value measured by gel permeation chromatography (GPC).

[0110] The “glass transition temperature” of a resin can be measured by a method known in the technical field, and for example, can be shown as a value measured by differential scanning calorimetry (DSC).

[0111] [Example]

[0112] Example and Comparative Example: Preparation of Water-Soluble Primer Composition

[0113] According to the components shown in Tables 1 to 3 below, various ingredients were stirred and mixed to prepare a water-soluble base oil composition, the viscosity of which at 25° C. was 55 seconds based on a No. 4 viscosity cup.

[0114]

Table 1

[0115]

[0116]

[0117]

Table 2

[0118]

[0119]

[0120]

Table 3

[0121]

[0122] The manufacturers and product names of various components used in the comparative examples and examples are shown in Table 4 below.

[0123]

Table 4

[0124]

[0125]

[0126] Test example: Evaluation of properties of the produced coating film

[0127] A middle-grade coating (manufacturer: KCC, product name: FU2290) was applied to the test piece and dried to form a middle-grade coating film. Then, on a flat surface, the water-soluble primer composition of Examples 1 to 21 and Comparative Examples 1 to 11 was applied by a rotary cup at a thickness of 15 μm. Then, air was blown at 80°C for 3 minutes to evaporate (dry) the residual water in the coating. A clear coat (manufacturer: KCC) was applied to the primer at a thickness of 40 μm, placed in an oven, and cured at 140°C for 25 minutes to form a final coating film. The appearance characteristics and physical properties of the final coating film were tested by the following methods, and the results are recorded in Tables 5 to 7.

[0128] (1) Coating workability

[0129] When the water-soluble primer composition is applied by the rotary cup, the coating workability is evaluated based on the spray state of the composition. The spray state is checked and judged, and a comparative evaluation is performed based on the micronization state.

[0130] (2) Appearance

[0131] The CF value of the final coating film was tested using the automobile appearance tester Wave Scan DOI (BYK Gardner). It is believed that the higher the CF value, the better the appearance characteristics of the coating film. Specifically, when the CF value is 65 or more, it is evaluated as excellent (◎), when it is 60 or more and less than 65, it is evaluated as good (○), when it is 55 or more and less than 60, it is evaluated as fair (△), and when it is less than 55, it is evaluated as poor (×).

[0132] (3) Gloss

[0133] The 20° gloss of the final coating film was tested. A gloss value of 90 or more was evaluated as excellent (◎), 88 or more and less than 90 was evaluated as good (○), 86 or more and less than 88 was evaluated as fair (△), and less than 86 was evaluated as poor (×).

[0134] (4) Fit

[0135] The primer compositions and clear coat compositions of Examples 1 to 21 and Comparative Examples 1 to 11 were applied and cured, and then the adhesion was evaluated using the go-eye method.

[0136] Specifically, the go-eye method was used to cut 100 squares (2 mm horizontally × 2 mm vertically) horizontally and vertically on the re-coated coating film with a knife blade, and then the film was torn with tape to test the adhesion. At this time, when 100% of the 100 squares were completely adhered, it was evaluated as excellent (◎), when the remaining squares were more than 70% and less than 100%, it was evaluated as good (○), when more than 50% and less than 70%, it was evaluated as fair (△), and when it was less than 50%, it was evaluated as poor (×).

[0137] (5) Impact resistance

[0138] A 500g weight was dropped from a height of 30cm onto the final coating film. At this time, the surface of the final coating film was observed and the impact resistance was evaluated. Specifically, when there were no cracks (CRACK) or traces of impact on the surface, it was evaluated as excellent (◎), when there were traces, it was evaluated as fair (△), and when there were cracks or cracks on the final coating film, it was evaluated as poor (×).

[0139] (6) Water resistance

[0140] The final coating film was immersed in a constant temperature bath at 40°C for 10 days, and then the adhesion was tested by the same method as the go-eye method in item (4). The water resistance of the coating film was also evaluated using the same evaluation criteria.

[0141] (7) Paint fluidity

[0142] A test piece with a middle coating film formed was vertically suspended, and the water-soluble primer composition of Examples 1 to 21 and Comparative Examples 1 to 11 was coated in the same manner as described above. After drying and curing, the surface of the coating film was observed and the paint fluidity of the composition was evaluated.

[0143] A hole with a diameter of 5 mm was punched on the pre-coated steel plate. After applying the above middle and clear coats, the paint condensed at the lower end of the hole was observed. The film thickness μm of the final coating at the observation time point when flow occurred was recorded as the flow limit film thickness. At this time, it is believed that the smaller the value of the detected flow limit film thickness is, the less fluid the paint is.

[0144] Specifically, when the flow limit film thickness is 40 μm or more, it is evaluated as excellent (◎), when it is 35 μm or more and less than 40 μm, it is evaluated as good (○), when it is 30 μm or more and less than 35 μm, it is evaluated as fair (△), and when it is less than 30 μm, it is evaluated as poor (×).

[0145] (8) Resistance to cold fracture

[0146] The final coating film was placed at -20°C for 3 hours, and then 50g of fine stone was squeezed out at 4 bar pressure to hit the surface of the final coating film. At this time, the damaged part of the final coating film was evaluated as excellent (◎) when it was less than 1mm, good (○) when it was more than 1mm and less than 2mm, fair (△) when it was more than 2mm and less than 3mm, and poor (×) when it was more than 3mm.

[0147] (9) Re-coating adhesion

[0148] The primer and varnish in the final coating film were stripped, and then the water-soluble primer composition and varnish of Examples 1 to 21 and Comparative Examples 1 to 11 were re-coated and cured in the same manner as above to prepare a re-coated coating film. Then, the adhesion of the re-coated coating film was tested by the go-eye method.

[0149] Specifically, the fit was tested using the same method and evaluation criteria as the Go method in item (4).

[0150]

Table 5

[0151]

[0152]

Table 6

[0153]

[0154]

Table 7

[0155]

[0156] As shown in Tables 5 to 7, in the property evaluation test of the prepared coating films, all physical properties of the water-soluble primer compositions of Examples 1 to 21 were evaluated as excellent, good or fair.

[0157] However, in Comparative Example 1 not containing the first acrylic resin, the coating film appearance, gloss and impact resistance were evaluated as poor, and Comparative Example 2 not containing the second acrylic resin was evaluated as poor in impact resistance and cold-crack resistance.

[0158] In Comparative Example 3 containing no polyurethane dispersion resin, the coating film appearance, adhesion, impact resistance, water resistance, cold-crack resistance, and recoating adhesion were evaluated as poor.

[0159] In Comparative Example 4, the glass transition temperature of the first acrylic resin did not reach the numerical range of the present invention, and its impact resistance, water resistance and cold crack resistance were evaluated as poor. In Comparative Example 5, the glass transition temperature of the first acrylic resin exceeded the numerical range of the present invention, and its coating film appearance, gloss and cold crack resistance were evaluated as poor.

[0160] In Comparative Example 6, the weight average molecular weight of the first acrylic resin did not reach the numerical range of the present invention, and its adhesion, impact resistance, water resistance and cold crack resistance were evaluated as poor. In Comparative Example 7, the weight average molecular weight of the first acrylic resin exceeded the numerical range of the present invention, and its coating workability, coating appearance, gloss and impact resistance were evaluated as poor.

[0161] In Comparative Example 8, the glass transition temperature of the second acrylic resin did not reach the numerical range of the present invention, and its coating appearance, gloss, impact resistance, water resistance and cold crack resistance were rated as poor. In Comparative Example 9, the glass transition temperature of the second acrylic resin exceeded the numerical range of the present invention, and its coating appearance, adhesion, impact resistance and re-coating adhesion were rated as poor.

[0162] In Comparative Example 10, the weight average molecular weight of the second acrylic resin did not reach the numerical range of the present invention, and its adhesion, impact resistance, water resistance and cold crack resistance were evaluated as poor. In Comparative Example 11, the weight average molecular weight of the second acrylic resin exceeded the numerical range of the present invention, and its coating film appearance, water resistance, paint fluidity and cold crack resistance were evaluated as poor.

[0163] Hereinafter, various embodiments of the present invention are described.

[0164] (1) The water-soluble primer composition comprises a first acrylic resin, a second acrylic resin, a polyurethane dispersion resin, a polyester resin, a polyurethane resin and a melamine-based curing agent, wherein the first acrylic resin has a glass transition temperature of 15 to 25° C. and a weight average molecular weight of 11,000 to 15,000 g / mol, and the second acrylic resin has a glass transition temperature of 1 to 10° C. and a weight average molecular weight of 5,000 to 10,000 g / mol.

[0165] (2) In the water-soluble base oil composition, the first acrylic resin has a hydroxyl value of 11 to 20 mgKOH / g and an acid value of 1 to 10 mgKOH / g, and the second acrylic resin has a hydroxyl value of 1 to 10 mgKOH / g and an acid value of 11 to 20 mgKOH / g.

[0166] (3) In the water-soluble base oil composition, the polyurethane dispersion resin has a glass transition temperature of -45 to -20°C, a weight average molecular weight of 35,000 to 60,000 g / mol, and an acid value of 15 to 30 mgKOH / g.

[0167] (4) In the water-soluble base oil composition, the polyester resin has a glass transition temperature of -50 to -25°C, a weight average molecular weight of 6,000 to 12,000 g / mol, a hydroxyl value of 80 to 110 mgKOH / g, and an acid value of 1 to 10 mgKOH / g.

[0168] (5) In the water-soluble base oil composition, the polyurethane resin has a glass transition temperature of -40 to -10°C, a weight average molecular weight of 200 to 900 g / mol, and an acid value of 15 to 30 mgKOH / g.

[0169] (6) Based on the total weight of the water-soluble base oil composition, the water-soluble base oil composition comprises 5 to 15 wt % of a first acrylic resin, 5 to 15 wt % of a second acrylic resin, 0.1 to 5 wt % of a polyurethane dispersion resin, 1 to 5 wt % of a polyester resin, 1 to 5 wt % of a polyurethane resin, and 3 to 8 wt % of a melamine-based curing agent.

Claims

1. A water-soluble base oil composition, characterized in that: The invention comprises a first acrylic resin, a second acrylic resin, a polyurethane dispersion resin, a polyester resin, a polyurethane resin and a melamine-based curing agent, The first acrylic resin has a glass transition temperature of 15 to 25° C. and a weight average molecular weight of 11,000 to 15,000 g / mol, The second acrylic resin has a glass transition temperature of 1 to 10° C. and a weight average molecular weight of 5,000 to 10,000 g / mol.

2. The water-soluble base oil composition according to claim 1, characterized in that: The first acrylic resin has a hydroxyl value of 11 to 20 mgKOH / g and an acid value of 1 to 10 mgKOH / g, The second acrylic resin has a hydroxyl value of 1 to 10 mgKOH / g and an acid value of 11 to 20 mgKOH / g.

3. The water-soluble base oil composition according to claim 1, characterized in that: The polyurethane dispersion resin has a glass transition temperature of -45 to -20°C, a weight average molecular weight of 35,000 to 60,000 g / mol, and an acid value of 15 to 30 mgKOH / g.

4. The water-soluble base oil composition according to claim 1, characterized in that: The polyester resin has a glass transition temperature of -50 to -25°C, a weight average molecular weight of 6,000 to 12,000 g / mol, a hydroxyl value of 80 to 110 mgKOH / g, and an acid value of 1 to 10 mgKOH / g.

5. The water-soluble base oil composition according to claim 1, characterized in that: The polyurethane resin has a glass transition temperature of -40 to -10°C, a weight average molecular weight of 200 to 900 g / mol, and an acid value of 15 to 30 mgKOH / g.

6. The water-soluble base oil composition according to claim 1, characterized in that: Based on the total weight of the water-soluble base oil composition, it includes 5 to 15 weight % of a first acrylic resin, 5 to 15 weight % of a second acrylic resin, 0.1 to 5 weight % of a polyurethane dispersion resin, 1 to 5 weight % of a polyester resin, 1 to 5 weight % of a polyurethane resin and 3 to 8 weight % of a melamine-based curing agent.

Citation Information

Patent Citations

  • Waterborne high glossy black basecoat paint composition and waterborne high glossy transparent topcoat paint composition

    KR101221276B1

  • Coating material composition and coated article

    CN105612227A

  • Aqueous paint composition for vehicle primer coating and vehicle coating method using same

    CN108603072A

  • Aqueous coating composition and method for producing aqueous coating composition

    CN112313297A

  • Detachable Face and Neck Sunshade

    KR1020210103350A